Linguistic Notes on the Globalization of Spanish Sport in Asia - Jesús Castañón-Rodríguez; Sergio Ricardo Quiroga (CV. FOUNDAE, 2024)
This study examines the internationalization and globalization of Spanish sports, particularly football in Asia and its cultural and linguistic influences. It aims to analyze the role of the Spanish language in advancing Spanish sports in Asian markets, focusing on the cultural impact of football and the use of linguistic products in education. Employing a descriptive approach, the research involves a bibliographic review and a systematic examination of institutional sources to gather data on the expansion of Spanish sport in Asia. The findings indicate that the globalization of sport has been propelled by technological progress and digital platforms, with English acting as the common language. Documented linguistic products include academic research, multilingual guides by the Instituto Cervantes and LaLiga, and the strategic application of Spanish in elite sports communication. These efforts showcase the global sports globalization process, emphasizing linguistic adaptation and promoting Spanish culture. In conclusion, the paper highlights sport as a vibrant arena for linguistic challenges and opportunities, aiding in the worldwide dissemination of the Spanish language. It points out the significance of linguistic products in overcoming cultural barriers and enhancing international relationships, with English as a pivotal lingua franca. The study offers valuable insights for further research and understanding of language and sports studies.